Composition and Dynamics of Bacterial Communities in a Full-Scale Mineral Water Treatment Plant - Wei, Lei; Wu, Qingping; Zhang, Jumei; Guo, Weipeng; Gu, Qihui; Wu, Huiqing; Wang, Juan; Lei, Tao; Chen, Moutong; Wu, Musheng; Li, Aimei (Frontiers in Microbiology, 2019)
The aim of this study was to gain insight into the bacteria composition and dynamics in a mineral water treatment system (MWTS). The bacterial community of a full-scale mineral water treatment plant in the Maofeng mountains of Southern China, was studied using high-throughput sequencing combined with cultivation-based techniques in both the dry and wet season. Overall, the microbial activity and biomass of water samples in the wet season were slightly lower than those in the wet season throughout the whole MWTS. The microbial activity and biomass of water samples obviously changed along with treatment process. All 300 isolates obtained using cultivation-based techniques were distributed in 5 phyla, 7 classes, and 19 genera. Proteobacteria accounted for 55.7% (167) of the total isolates, among which predominant species comprised Pseudomonas (19.3%) at the genus level. Illumina sequencing analysis of 16s rRNA genes revealed 15 kinds of bacterial phylum (relative abundance > 0.1) as being identified in all water samples. Among these, Proteobacteria constituted the dominant bacteria flora in all water samples, which was consistent with the results of the cultivation-based analyses. A large shift in the proportion of Bacteroidetes, Actinobacteria, and Firmicutes was obtained during the treatment process, with the proportion of Bacteroidetes, Actinobacteria decreasing sharply, whereas that of Firmicutes increased and predominated in the finished water product. The core microbiome, which was still present in the whole MWTS comprised several opportunistic pathogens, including Pseudomonas, Acinetobacter, Clostridium, and Mycobacterium, suggesting a potential threat for mineral water microbiology safety. This study is the first to investigate the bacterial community of a full-scale mineral water treatment plant in China. The results provide data regarding the bacteria composition and dynamics in an MWTS, which will contributed to the beneficial manipulation of the mineral water microbiome.